Systemic Inflammation Is Associated With Neurologic Involvement in Pediatric Inflammatory Multisystem Syndrome Associated With SARS-CoV-2. Issue 4 (July 2021) - Sa, Mario; Mirza, Luwaiza; Carter, Michael; Carlton Jones, Lalani; Gowda, Vasantha; Handforth, Jennifer; Hedderly, Tammy; Kenny, Julia; Lascelles, Karine; Lin, Jean-Pierre; Lumsden, Daniel; McDougall, Marilyn; et al.
Abstract : Objective: Pediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS) is a severe immune-mediated disorder. We aim to report the neurologic features of children with PIMS-TS. Methods: We identified children presenting to a large children's hospital with PIMS-TS from March to June 2020 and performed a retrospective medical note review, identifying clinical and investigative features alongside short-term outcome of children presenting with neurologic symptoms. Results: Seventy-five patients with PIMS-TS were identified, 9 (12%) had neurologic involvement: altered conciseness (3), behavioral changes (3), focal neurology deficits (2), persistent headaches (2), hallucinations (2), excessive sleepiness (1), and new-onset focal seizures (1). Four patients had cranial images abnormalities. At 3-month follow-up, 1 child had died, 1 had hemiparesis, 3 had behavioral changes, and 4 completely recovered. Systemic inflammatory and prothrombotic markers were higher in patients with neurologic involvement (mean highest CRP 267 vs 202 mg/L, p = 0.05; procalcitonin 30.65 vs 13.11 μg/L, p = 0.04; fibrinogen 7.04 vs 6.17 g/L, p = 0.07; D-dimers 19.68 vs 7.35 mg/L, p = 0.005). Among patients with neurologic involvement, these markers were higher in those without full recovery at 3 months (ferritin 2284 vs 283 μg/L, p = 0.05; D-dimers 30.34 vs 6.37 mg/L, p = 0.04). Patients with and without neurologic involvement shared similar risk factors for PIMS-TS (Black, Asian and Minority Ethnic ethnicity 78% vs 70%, obese/overweight 56% vs 42%). Conclusions: Broad neurologic features were found in 12% patients with PIMS-TS. By 3-month follow-up, half of these surviving children had recovered fully without neurologic impairment. Significantly higher systemic inflammatory markers were identified in children with neurologic involvement and in those who had not recovered fully.